Endoscopic Epidurolysis for the Management of Chronic Spinal Pain: A Delphi-Based Italian Experts Consensus - Matteo Luigi Giuseppe Leoni; Felice Occhigrossi; Michael Tenti; William Raffaeli; ISAL Research Study Group (Pain and Therapy)
Abstract Introduction Endoscopic epidurolysis (EE) is a minimally invasive procedure used to manage chronic spinal pain, particularly in cases unresponsive to traditional treatments. Despite its growing recognition, the literature lacks comprehensive guidelines on its optimal use. This study utilized a modified Delphi approach to gather expert consensus on best practices for EE in the Italian pain therapy network. Methods The study’s scientific board conducted an extensive literature review to define key investigation topics, including clinical indications, preoperative assessments, and technical aspects of EE. A semi-structured questionnaire was developed and administered to a panel of experts. A two-round Delphi process was implemented, with consensus defined as at least 70% agreement on a 7-point Likert scale (agree or strongly agree). Statements that did not reach consensus in the first round were rephrased and resubmitted in the second round. Results Twenty-six clinicians participated in the study, with a 100% response rate in both rounds. In the first round, consensus was achieved for 9 out of 19 statements. In the second round, 8 out of 10 rephrased statements reached the consensus threshold. Key areas of agreement included the clinical indications for EE, the importance of preoperative imaging and anesthetic assessments, and the use of specific techniques and tools for EE. However, consensus was not reached on the use of EE for disc herniation with radicular pain and the safety of interlaminar access compared to sacral hiatus access. Conclusion The study highlights the need for standardized protocols in EE to ensure consistent and effective treatment of chronic spinal pain. The consensus reached by the expert panel provides a framework for best practices, which can guide clinical decision-making and improve patient outcomes. Further research is necessary to validate these findings and address areas where consensus was not achieved.